High Curie temperature in Zn(Co,Ni)Se: DFT study - Jafarova, Vusala Nabi; Hashimova, Nermin Neriman; Scurtu, Ionut Cristian (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
In this work, we aimed to examine the first-principles study of correlation between chemical environment and ferromagnetism, and Curie temperature of CoxZn1-xSe and NixZn1-xSe diluted magnetic semiconductors for different concentrations of impurity atoms. The calculations are implemented by the norm-concerving FHI pseudopotential method within the local spin density approximation (LSDA) and Hubbard U method. The analysis of the total density of states curves shows the half-metallic ferromagnetic character with half-metallic band gap. The first-principles calculated total magnetic moments of CoxZn1-xSe and NixZn1-xSe systems are found to be equal to 3 and 4 µB, respectively.